PENGARUH VARIASI KECEPATAN POTONG PAHAT HSS PENGEBORAN BAJA S45C/AISI 1045 TERHADAP MEDIA PENDINGIN PADA UJI KEKERASAN DAN STUKTUR MIKRO - Duniawan, Agus (ReTII, 2017)
ABSTRACT The development of science and technology in manufacturing industry continues to grow, particular in machineries. One of many machineries in production is drilling machine. Cooling medium is important factor in drilling process. The research aims to figure out the effect of cooling medium (water and lubricant oil) on mechanical and physical properties on HSS drill when used for drilling of S45C steel / AISI 1045. HSS drill has composition of 0.75% -1.5% (C), 4% -4.5% (Cr), 10% -20% (W) and (Mo), 5% (V) and more than 12% Cobalt (Co). The research is conducted at spinde speed and drill velocity of 640-970 rpm and 20-30 m/minute, respectively. The result shows that HSS drill’s harness is the highest for cooling medium of lubricant oil. Thi is due to microstructure of ferit and carbon and also affacted by Cr and Mn. The hardness of HSS drill is higher in cooling medium of lubricant oil compared than in cooling medium of water. At drill velocity of 20 m/minute, the hardness of HSS drill is 62,3 HRC for cooling medium of water and 63, 7 HRC for cooling medium of lubricant oil. Meanwhile, at 30 m/minute drill velocity, the hardness of HSS drill is 63,7 HRC for cooling medium of water and 64, 7 HRC for cooling medium of lubricant oil. Keywords: Mechanical properties, cooling medium, cutting speed